Last: A Tragicomedy in Six Scenes. - Hoover, Jacob T., II. (Tufts Archival Research Center, 2016)
Last is an absurd tragicomedy about the final act of the human race. In a future where the last human being is nothing more than a scientific curiosity on display, this final member of our species tries to remember what humanity was and how it should be remembered.